Associations between non-motor symptoms and patient characteristics in Parkinson’s disease: a multicenter cross-sectional study - Morimoto, Remi; Iijima, Mutsumi; Okuma, Yasuyuki; Suzuki, Keisuke; Yoshii, Fumihito; Nogawa, Shigeru; Osada, Takashi; Kitagawa, Kazuo (Frontiers in Aging Neuroscience, 2023)
Objective: Parkinson's disease (PD) is characterized by various non-motor symptoms (NMS), such as constipation, olfactory disturbance, sleep disturbance, mental disorders, and motor symptoms. This study aimed to investigate factors associated with NMS in patients with PD. Methods: Symptoms of PD were evaluated using the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS), Parts I–IV. NMS was assessed using the MDS-UPDRS Part I (self-assessment of NMS) and rapid eye movement sleep behavior disorder (RBD) questionnaires. Patients were categorized by age into < 70 years and ≥ 70 years (older adults) groups, according to disease duration into early-stage and advanced-stage groups with a cut-off value of 5 years for motor symptoms, and by sex into male and female groups. Results: A total of 431 patients with PD (202 males and 229 females) with a mean age of 67.7 years, a mean disease duration of 6.4 years, and a mean Part I total score of 9.9 participated in this study. The Part I total score was significantly positively correlated (p<0.01) with disease duration and Part II, III, and IV scores. For Part I sub-item scores, the older group had significantly higher scores for cognitive impairment, hallucinations, sleep problems, urinary problems, and constipation than the < 70 years group, whereas the advanced-stage group had significantly higher scores for hallucinations, sleep problems, daytime sleepiness, pain, urinary problems, and constipation (p<0.05) than the early-stage group. Anxiety was higher in female patients than in male patients, whereas daytime sleepiness, urinary problems, and RBD were higher in male patients than in female patients (p<0.05). Factors affecting Part I included disease duration, Part II total scores, Part IV total scores, and RBD. Conclusion: According to the self-questionnaire assessment, NMS was highly severe in older adult patients, those with longer illness duration, subjective and objective motor function impairments, and RBD. Sex-based differences were also observed.